2018
DOI: 10.1007/s10571-018-0578-5
|View full text |Cite
|
Sign up to set email alerts
|

Cuprizone Administration Alters the Iron Metabolism in the Mouse Model of Multiple Sclerosis

Abstract: Cuprizone (CZ) is a widely used copper chelating agent to develop non-autoimmune animal model of multiple sclerosis, characterized by demyelination of the corpus callosum (CC) and other brain regions. The exact mechanisms of CZ action are still arguable, but it seems that the only affected cells are the mature oligodendrocytes, possibly via metabolic disturbances caused by copper deficiency. During the pathogenesis of multiple sclerosis, high amount of deposited iron can be found throughout the demyelinated ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Abnormal iron deposition in the subcortical gray matter anatomic structures is a known pathological feature of MS [15,64,65]. A growing body of evidence suggests that an altered iron metabolism is closely associated with myelin pathology in both human MS disease and animal demyelination models [66,67,68,69]. Sensitivity to tissue relaxation properties is a known problem in alternative approaches for myelin imaging, such as multi-component relaxation methods [70,71,72] and MTR, while MPF mapping overcomes this limitation [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal iron deposition in the subcortical gray matter anatomic structures is a known pathological feature of MS [15,64,65]. A growing body of evidence suggests that an altered iron metabolism is closely associated with myelin pathology in both human MS disease and animal demyelination models [66,67,68,69]. Sensitivity to tissue relaxation properties is a known problem in alternative approaches for myelin imaging, such as multi-component relaxation methods [70,71,72] and MTR, while MPF mapping overcomes this limitation [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Cuprizone (CPZ) is synthesised by combining cyclohexanone and oxaldihydrazone [38]. While the mechanism of its toxic actions remain ill-defined, copper chelation [39] and dis-homeostasis of iron, zinc, sodium and manganese have been reported [40,41,42,43,44]. Such ion imbalance leads to endoplasmic reticulum stress, reduced mitochondrial ATP synthesis, and increased production of reactive oxygen and nitrogen species (reviewed in [2]).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we examined the effect of CZ on iron metabolism regulation both locally in the brain and systemically via the hormone hepcidin produced by the liver [49]. The reason for these experiments was that there is evidence that the metabolisms of the two ions (iron and copper) are closely related [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments revealed that cuprizone as a copper chelating agent affected the iron metabolism in brain and liver tissues following four-week long cuprizone treatment [49]. To determine the early effect of CZ treatment on iron homeostasis regulation, cytosolic and mitochondrial iron storage, as well as some lipid metabolism genes we investigated the expression of respective iron homeostasis and lipid metabolism genes of the corpus callosum (CC) and the liver after short-term (two and eight days) CZ administration.…”
Section: Introductionmentioning
confidence: 99%